In vitro pharmacodynamics of fosfomycin against clinical isolates of Pseudomonas aeruginosa. (24th July 2015) - Walsh, Clare C.; McIntosh, Michelle P.; Peleg, Anton Y.; Kirkpatrick, Carl M.; Bergen, Phillip J.
Abstract : Background: The use of fosfomycin for treatment of systemic infections due to MDR Pseudomonas aeruginosa is increasing. However, pharmacodynamic data for fosfomycin are limited. Methods: Sixty-four clinical isolates of P. aeruginosa (MDR and non-MDR) from two Australian hospitals were collected; 59 isolates were from patients with cystic fibrosis and 5 isolates were from critically ill patients. The in vitro pharmacodynamic properties of fosfomycin (disodium) were investigated via MICs (all isolates) and, for selected isolates, via time–kill kinetics (static and dynamic models; concentration range, 1–1024 mg/L), population analysis profiles (PAPs) and post-antibiotic effect (PAE). Two inocula (∼10 6 and ∼10 8 cfu/mL) were included in static time–kill studies to examine the effect of inocula on bacterial killing. Results: MICs ranged from 1 to >512 mg/L, with 61% of isolates considered fosfomycin susceptible (MIC ≤64 mg/L). The MIC distributions for MDR and non-MDR isolates were similar. Baseline PAPs indicated heteroresistance in all isolates tested. Time–kill studies showed moderate (maximum killing ∼3 log10 cfu/mL), time-dependent killing at the low inoculum with regrowth at 24 h. Most concentrations resulted in complete replacement of fosfomycin-susceptible colonies by fosfomycin-resistant colonies. Bacterial killing was virtually eliminated at the high inoculum. The PAE ranged from 0.3 to 5.5 h. Conclusions: These data suggest monotherapy with fosfomycin may be problematic for the treatment of infections caused by P. aeruginosa . Further investigation of fosfomycin combination therapy is warranted.